1989
DOI: 10.1159/000167987
|View full text |Cite
|
Sign up to set email alerts
|

Foscarnet Nephrotoxicity: Mechanism, Incidence and Prevention

Abstract: Foscarnet is a pyrophosphate analogue that has been successfully used in severe cytomegalovirus (CMV) infections. Little is known of the incidence and mechanisms of foscarnet-induced nephrotoxicity as most data comes from recipients of renal allografts or from patients with severe underlying disease or with other nephrotoxic drugs. We have retrospectively analyzed the evolution of renal function after 56 courses of foscarnet. In addition, we have prospectively studied the protective effects of hydration on fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(83 citation statements)
references
References 22 publications
3
78
0
2
Order By: Relevance
“…The relationship of renal insufficiency to foscarnet use was considered possible in 4 of these 5 patients and was judged unevaluatable in the other. The frequency and severity ofrenal toxicity in our study was in the range ofthat in other studies ofallogeneic BMT recipients and AIDS patients [24,25,[28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The relationship of renal insufficiency to foscarnet use was considered possible in 4 of these 5 patients and was judged unevaluatable in the other. The frequency and severity ofrenal toxicity in our study was in the range ofthat in other studies ofallogeneic BMT recipients and AIDS patients [24,25,[28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 62%
“…In that study, only 1 (4%) of27 patients with AIDS and CMV retinitis who received foscarnet with hydration developed acute renal failure. Peak serum creatinine levels in this group of patients were significantly lower than in a historical control group that had received the same foscarnet regimen without hydration [32]. Reduction of renal toxicity would allow a larger proportion of BMT recipients to receive a full course of foscarnet prophylaxis, which may reduce the incidence of CMV infection after transplant.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is used in immune-compromised patients with life-threatening herpes simplex or cytomegalovirus infections [98,99]. Intensive IV hydration dramatically reduces the incidence of foscarnet-induced acute kidney injury [100]. Foscarnet can lead to acute tubular toxicity; rarely, a direct effect on tubular function can be detected, which may lead to mitochondrial dysfunction, inducing mitochondrial DNA (mtDNA) in renal tubule cells [101].…”
Section: Foscarnetmentioning
confidence: 99%
“…Prehydration with intravenous saline reduces the risk of nephrotoxicity. 24 In a previous study we have shown that foscarnet can prevent CMV infections in patients receiving T celldepleted grafts. 18 We are now reporting a dose-finding study for CMV prophylaxis, designed to test: (a) safety and tolerability of foscarnet; (b) efficacy in preventing CMV Bone Marrow Transplantation disease; and (c) influence of foscarnet prophylaxis on engraftment kinetics.…”
mentioning
confidence: 97%